2021
DOI: 10.24191/ajue.v17i3.14499
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Pre-Service Teachers' Practical Knowledge and Motivation about Artificial Intelligence through a Service-learning-based Module in Guizhou, China: A Quasi-Experimental Study

Abstract: Abstract. The purpose of this study is twofold: 1) to develop a service-learning-based module training artificial intelligence (AI) subject (SLBM-TAIS), and 2) to evaluate the effect of SLBM-TAIS on pre-service teachers’ (PSTs’) practical knowledge and motivation, as well as primary school students' attitude towards AI in China. Participants of this study comprised 60 PSTs and 107 primary school students. The experimental research in this study followed the quasi-experimental non-randomized pre-test and post-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Behavior when using AI and LA [31,35,39,40,42,44,52] 7 Digital competence [34,38,45,50,53,58] 6 Perception of AI and LA [32,41,48,56,60] 5 Self-regulation and reflection [33,35,47,54,55] 5 Engagement [36,51,57,59] 4 Analysis of educational data [37,43,49] 3…”
Section: Goals and Objectives Reference Number Number Of Studiesmentioning
confidence: 99%
“…Behavior when using AI and LA [31,35,39,40,42,44,52] 7 Digital competence [34,38,45,50,53,58] 6 Perception of AI and LA [32,41,48,56,60] 5 Self-regulation and reflection [33,35,47,54,55] 5 Engagement [36,51,57,59] 4 Analysis of educational data [37,43,49] 3…”
Section: Goals and Objectives Reference Number Number Of Studiesmentioning
confidence: 99%
“…With the project citizen model there are six stages in preparing the student work program, namely: identifying problems, choosing problems, collecting information, fortofolio documents, reflecting studies and, determining the solution of the problem. The results showed that through the learning model project citizen experienced several positive influences, namely; (1) students enjoy the implementation of practical activities; (2) students have the opportunity to study various problems to be solved; (3) Students can understand how to position themselves in seeing others; (4) students experiencing conditions must face the obstacles of different ways of solving problems, and; (5) students can learn the culture of the communities they serve; (6) may determine policy alternatives to the issue. Thus it can be blinded that student involvement in the community through the project citizen model can bring change.…”
Section: Discussionmentioning
confidence: 99%
“…Campus as an academic environment is responsible for managing and involving students in various community-based fundamental projects. Life skills and student participation that develops after participating in community activities aim to increase self-potency (civic skills) and individual responsibilities as part of a community [2].…”
Section: Introductionmentioning
confidence: 99%
“…The onus falls on students to proactively take the initiative in their learning endeavors, fostering a positive disposition conducive to favorable learning outcomes. Hu & McGeown, (2020); Mentang et al, (2022); Pu et al, (2021) posit that effective communication in language learning hinges upon adept deployment of language skills. Consequently, learners who flourish in autonomous learning environments characterized by interactive engagement are more adept at acquiring a diverse repertoire of language skills.…”
Section: Introductionmentioning
confidence: 99%